Pilot Study on the Effects of the Teaching Interpersonal Skills Program for Teens Program (PEHIA) - Serrano-Pintado, Isabel; Escolar-Llamazares, María-Camino; Delgado-Sánchez-Mateos, Juan (Frontiers in Psychology, 2022)
Background/Objective: Social skills are essential in adolescence, both for their relational dimension and for their influence on other areas of the adolescent's life, so it is essential to include Social skills their instruction in the formal education of students. Method: This paper presents the results of a pilot study in which an Interpersonal Skills Training Program for Adolescents (PEHIA ) was applied. The sample consisted of 51 adolescents. The An evaluation was carried out before and after the intervention using the CEDIA (Adolescent Interpersonal Difficulties Assessment Questionnaire) and SAS-A (Social Anxiety Scale for Adolescents) questionnaires. Results: The results show significant differences in the overall measures and in most of the subscales of both questionnaires, indicating that PEHIA is effective, at least in the short term. Conclusions: The results obtained in assertiveness, interpersonal relationships and public speaking suggest that the program wasis feasible and holdshows promising results in reducing anxiety. However, a larger scale study should be conducted that the earlier, in adolescence, a structured training in interpersonal skills is started, the better results will be achieved.